Bacteriological Profile of Neonatal Sepsis in a Tertiary Level Hospital of Nepal - Khanal, R; Manandhar, S; Acharya, GP (Journal of Nepal Paediatric Society, 2015)
Introduction: Neonatal sepsis is one of the most common reasons for admission to neonatal units in developing countries. It is also a major cause of mortality in both developed and developing countries. This study was done to determine the bacterial profile causing neonatal sepsis and to assess their susceptibility pattern to various antimicrobial agents. Materials and Methods: A cross-sectional prospective study was conducted in Paropakar Maternity and Women’s Hospital, Kathmandu, Nepal among 340 neonates suspected of neonatal sepsis. Blood culture was performed and organisms were identified with Gram staining and conventional biochemical methods. Antimicrobial susceptibility testing was performed by Kirby-Bauer disk diffusion method according to the Clinical and Laboratory Standards Institute (CLSI). Results: The prevalence rate of neonatal sepsis was 20.3%. Among 340 neonates, 52.17% were males and 47.82% were females. Gram positive cocci were the most predominant isolates (88.40%). Among Gram positive cocci Staphylococcus epidermidis was the most common isolates (72.46%) followed by Staphylococcus aureus (7.24%), Staphylococcus saprophyticus (4.34%) and Enterococcus fecalis (4.34%). Gram negative bacilli were found in 11.60% of the growth positive samples of which E.coli and Klebsiella spp were found in 10.14% and 1.44% respectively. Sensitivity to Amikacin was highest among all types of organisms isolated. Vancomycin and Gentamycin sensitivity was highest for Gram positive and Gram negative organisms respectively. Ampicillin resistance was highest among isolates. Among the 69 isolates 48 were Multiple drug resistant. Conclusion: The predominance of Gram positive cocci particularly Coagulase negative Staphylococci is shown. Empirical antibiotic therapy should be reviewed for Multiple drug resistant strains. DOI: http://dx.doi.org/10.3126/jnps.v34i3.9183 J Nepal Paediatr Soc 2014;34(3):175-180